Clinical Evaluation of Uttar Basti and some Herbo- Mineral Compounds in Female Infertility - Bandil, Bharti (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Infertility is an emerging health problem that has profound socioeconomic and health implication on both the individual and society. Ayurveda explained female infertility as Vandhyatva and mentioned Garbha Sambhava Samagri (proper union of four factors like fertile period, healthy reproductive system, nutrition and healthy ovum and sperm) and Manasika Abhitapa (psychological and emotional factors) as chief factors responsible for conception. The efficacy of Uttar basti of Kalyanak Ghrita with oral Garbhadharak yog with anupana of Ashwagandha Ksheerpaka mixed with Kalyanak Ghrita has encouraging effects for the management of primary cases of Bandhyatva. Methods: In this trial, randomly categorized the patients of primary infertility and grouped them into A, B & C who were ineligible for fertility after the several years of unprotected intercourses. The Group A patients were treated with Kalyanak Ghrita Uttarbasti, 3 days alternatively in a month for consecutive three cycle. The Group B patients were treated with Oral Garbhadharak Yoga while Group C patients were treated with Kalyanak Ghrita Uttarbasti and Oral Garbhadharak Yoga for three months consecutively. Result: Total 60 patients were investigated for Bandhyatva for present study. The effect of Uttar basti of Kalyanak Ghrita with oral yog (Garbhadharak yog with the anupana of Ashwagandha Ksheerpaka mixed with Kalyanak Ghrita) in Group C Patients Shows maximum relief in cervical mucus was 50.00%, Viscosity 65%, Spinnbarkeit formation 54.54%, cellularity 37.83% reduced Fern pattern on 22nd day was 48.27%, PCT 27.77%, Leucorrhea 83.33%, Amount of blood loss 17.50%, Regularity 71.42%, Dysmenorrhea 88.88%, and improvement in follicular growth was 54.16%. Conclusion: In Group C, out of 20 patients 05 patients were conceived showing 25% relief in primary infertility. The overall effectiveness of therapy in all studied 60 patients of primary infertility was 15%. The statistical analysis data of the clinical research work done on all 60 patients of infertility shows the highly significant result (p<0.001)